FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA SISWI SMAN 1 TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Alhidayati Alhidayati; Christine Vita Gloria Purba; Tri Murti Tri (JURNAL KESMAS DAN GIZI (JKG), 2019)
One of the phenomenal teen problems is nutritional problems. Iron nutrition anemia in adolescents is a condition where the hemoglobin (Hb) data of red blood cells is lower than the normal value due to iron deficiency. This study was aimed to determined the factors associated with the incidence of anemia in female students of SMAN 1 Tembilahan Hulu Indragiri Hilir Regency. This type of research was quantitative with Cross Sectional design. The study population was female students of SMAN 1 Tembilahan Hulu, Indragiri Hilir Regency and a sample of 82 people. Sampling was done by simple random sampling. The measuring instrument used a questionnaire. The analysis was carried out by univariate and bivariate. The results of statistical tests used the chi square test revealed that there was a relationship between knowledge (p = 0.048), attitude (p = 0.004), eating habits (p = 0.002), nutritional status (p = 0.030) with the incidence of anemia in female students of SMAN 1 Tembilahan Hulu Indragiri Hilir Regency. It is expected that the School can collaborate with the local Puskesmas in giving advice about anemia to young women in school for the knowledge and attitudes of young women about anemia problems which include signs of symptoms, complications, ways to prevent anemia and others.